Introduction to the Proceedings of the Workshop “Habits and Rituals” at IS4SI-2017 Gothenburg, Sweden, 15 June 2017 - Raffaela Giovagnoli; Gordana Dodig-Crnkovic (Proceedings, 2017)
Habits and rituals play a fundamental role in human life [1] and are worthy to be considered also because they represent a form of embodied knowledge. According to Dubray [2], habits can be studied in general, but also with the focus on their physiological, psychological, ethical, pedagogical, philosophical and theological aspects. [...]